2011
DOI: 10.1152/ajpheart.00018.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate improves circulation in postural tachycardia syndrome

Abstract: Stewart JM, Ocon AJ, Medow MS. Ascorbate improves circulation in postural tachycardia syndrome. Am J Physiol Heart Circ Physiol 301: H1033-H1042, 2011. First published May 27, 2011 doi:10.1152/ajpheart.00018.2011.-Low flow postural tachycardia syndrome (LFP) is associated with vasoconstriction, reduced cardiac output, increased plasma angiotensin II, reduced bioavailable nitric oxide (NO), and oxidative stress. We tested whether ascorbate would improve cutaneous NO and reduce vasoconstriction when delivered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…Additionally, Cracowski et al (2007) following a similar heat-reheat protocol, raising skin temperature at a rate of 0.09°C·s − 1 , also noted no differences in the thermal hyperemia response to a local heating stimulus (Cracowski et al, 2007). Thus, it seems as though the rapid rate of heating employed in the studies by Ciplak et al and Frantz et al may explain the conflicting results compared to those of protocols 1 and 2 of the present study and those previously published by others (Cracowski et al, 2007;Medow et al, 2011;Shastry and Joyner, 2002;Stewart et al, 2007a;Stewart et al, 2009;Stewart et al, 2011;Stewart et al, 2008a).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Additionally, Cracowski et al (2007) following a similar heat-reheat protocol, raising skin temperature at a rate of 0.09°C·s − 1 , also noted no differences in the thermal hyperemia response to a local heating stimulus (Cracowski et al, 2007). Thus, it seems as though the rapid rate of heating employed in the studies by Ciplak et al and Frantz et al may explain the conflicting results compared to those of protocols 1 and 2 of the present study and those previously published by others (Cracowski et al, 2007;Medow et al, 2011;Shastry and Joyner, 2002;Stewart et al, 2007a;Stewart et al, 2009;Stewart et al, 2011;Stewart et al, 2008a).…”
Section: Discussioncontrasting
confidence: 42%
“…In protocol 1, we examined the effect of a heat-reheat protocol on cutaneous vasodilatation at forearm and leg skin sites. Based on the work of Stewart and coworkers (Medow et al, 2011;Stewart et al, 2007a;Stewart et al, 2009;Stewart et al, 2011;Stewart et al, 2008a) we hypothesized that the vasodilator response to the second bout of heating would be the same as the first. In protocol 2, we examined the effect of NOS inhibition combined with the same (protocol 1) heat-reheating procedure.…”
Section: Introductionmentioning
confidence: 99%
“…*P Ͻ 0.05 compared with the control group. When present, systemic circulatory abnormalities are also found in the brain (34,55) and may account for impaired CBF autoregulation in the upright POTS patient (34). Impairment of cerebral autoregulation is associated with a reduction in neurovascular coupling (52) as well as cognition (33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mechanisms of acetylcholine (ACh)-induced vasodilatation remain to be fully understood and can certainly not be related to a single vasoactive mediator. Using retrodialysis, ACh-induced vasodilatation has been shown to involve release of both NO and prostaglandins [62,68,69] and, further, a study investigating splanchnic vasodilatation in normal-flow postural tachycardia syndrome showed that NO produced by endothelial NOS is released by ACh [70]. …”
Section: Retrodialysis In Experimental Human Studiesmentioning
confidence: 99%
“…Stewart et al [70] tested whether ascorbate would improve cutaneous NO and reduce vasoconstriction when delivered systemically using retrodialysis. Their data provided experimental support for the concept that oxidative stress and reduced NO contribute to vasoconstriction and venoconstriction in patients with low-flow postural tachycardia syndrome compared to healthy controls.…”
Section: Clinical Applications Of Retrodialysismentioning
confidence: 99%